Basic groupwork - Douglas, Tom (Routledge, 2000)
"Basic Groupwork is a simple, practical guide to the processes of groupwork. This new edition has been extensively updated and revised to reflect the changes which have taken place in society and social behaviour since it was first published in 1978, but in essence it remains an accessible and friendly text for the novice practitioner." "In logical sequence the book follows the progress of one group from inception to close and exposes how groups work." "Basic Groupwork provides students with a sound and solid basis for any kind of groupwork, in any context."--Jacket